2021
DOI: 10.3390/molecules26196053
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-Catalyzed Oxidation of Allylbenzene Derivatives: Towards a Green Equivalent of Ozonolysis

Abstract: Laccase-based biocatalytic reactions have been tested with and without mediators and optimized in the oxidation of allylbenzene derivatives, such as methyl eugenol taken as a model substrate. The reaction primarily consisted in the hydroxylation of the propenyl side chain, either upon isomerization of the double bond or not. Two pathways were then observed; oxidation of both allylic alcohol intermediates could either lead to the corresponding α,β-unsaturated carbonyl compound, or the corresponding benzaldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Citronellol is a monoterpenyl alcohol which can be converted into other derivatives, for example by oxidation. In the context of green and sustainable chemistry, the use of laccases is appropriate to convert citronellol into oxidized products with limited footprints, conventional oxidation processes being typically waste-generating (Lecourt et al 2021). However, the presence of laccase alone did not allow to convert citronellol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citronellol is a monoterpenyl alcohol which can be converted into other derivatives, for example by oxidation. In the context of green and sustainable chemistry, the use of laccases is appropriate to convert citronellol into oxidized products with limited footprints, conventional oxidation processes being typically waste-generating (Lecourt et al 2021). However, the presence of laccase alone did not allow to convert citronellol.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments showed that citronellol conversion did not reach 100%. Enzyme or mediator deactivation, or both, had to be considered (Lecourt et al 2021). Following this hypothesis and in order to improve conversion of citronellol, two experiments were performed in parallel, with either enzyme or mediator being added every 24 h (Figure 9).…”
Section: Iib Total Conversion Of Citronellol and Products Identificationmentioning
confidence: 99%
“…[17][18][19] Additionally, this group of enzymes was recently reported as an efficient catalyst for the radical dimerisation of phenol derivatives, 20,21 the synthesis of catechol thioethers 22 or the oxidation of allylbenzene derivatives. 23 Recently, we have established a chemoenzymatic laccasemediated cascade towards α-acyloxy carboxamides that involves simultaneous enzymatic oxidation with a multicomponent reaction MCR (Ugi or Passerini). 24,25 The published approach is a green and efficient alternative to existing methods.…”
Section: Introductionmentioning
confidence: 99%